2022
DOI: 10.1016/j.braindev.2021.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Breastfeeding and risk of febrile seizures in the first 3 years of life: The Japan Environment and Children’s Study

Abstract: Objective: Our study was conducted to examine the association between breastfeeding and febrile seizures (FS) in the first 3 years of life.Methods: We analyzed the dataset of the Japan Environment and Children's Study (JECS), which is a birth cohort study undertaken to elucidate the influence of environmental factors on children's health during the fetal period and early childhood. Information on feeding duration and feeding pattern, as well as information on febrile seizures, were obtained from questionnaires… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 23 publications
0
10
1
Order By: Relevance
“…In particular, undernutrition during infancy can affect cognitive development by causing direct structural damage to the brain and impairing infant motor system development and exploratory behavior [25]. However, studies of the potential impact of infant feeding on neurological diseases are scarce, and the findings of existing studies are not definitive [26][27][28]. A previous study reported a protective role of breastfeeding in febrile convulsion in the first year of life [27], and another study reported a small protective role of breastfeeding in febrile convulsions until 2 years of age [28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, undernutrition during infancy can affect cognitive development by causing direct structural damage to the brain and impairing infant motor system development and exploratory behavior [25]. However, studies of the potential impact of infant feeding on neurological diseases are scarce, and the findings of existing studies are not definitive [26][27][28]. A previous study reported a protective role of breastfeeding in febrile convulsion in the first year of life [27], and another study reported a small protective role of breastfeeding in febrile convulsions until 2 years of age [28].…”
Section: Discussionmentioning
confidence: 99%
“…However, studies of the potential impact of infant feeding on neurological diseases are scarce, and the findings of existing studies are not definitive [26][27][28]. A previous study reported a protective role of breastfeeding in febrile convulsion in the first year of life [27], and another study reported a small protective role of breastfeeding in febrile convulsions until 2 years of age [28]. However, no study has identified any associations of the diversity of infant diet with childhood neurologic diseases, including febrile convulsion, epilepsy, and ADHD.…”
Section: Discussionmentioning
confidence: 99%
“…In brief, sociodemographic, health, and lifestyle confounders in mother-infant dyads, which are associated with the incidence of childhood otitis media [3,5], were included in the analyses as covariates. The data retrieval was performed using medical transcription reports and self-administered questionnaires [32][33][34].…”
Section: Covariatesmentioning
confidence: 99%
“…Except for the influence of genetics, risk factors including a family history of FS, peak body temperature during the illness, low birth weight, and in utero growth retardation have been reported. The effects of prenatal exposure to smoking and alcohol are still under debate [2,4,5].…”
Section: Introductionmentioning
confidence: 99%
“…There is little evidence showing the association between breastfeeding and FS, and the effect of breastfeeding duration has scarcely been discussed [4,13]. Thus, the aim of this 2 of 8 study was to determine the association between breastfeeding and FS, and to discuss the influence of different breastfeeding durations.…”
Section: Introductionmentioning
confidence: 99%